The importance of a multisectoral One Health approach - Bett, Bernard K. (International Livestock Research Institute, 2021)
Bernard Bett, team leader, One Health Research, Education and Outreach Centre in Africa (OHRECA) at ILRI, explains why One Health requires a multisectoral approach ways of strengthening One Health in development programs. This film is part of the ILRI and CGIAR 'Investing in One Health' video series.